Sustainable Manufacturing through Green Entrepreneurship – The Only Way to Survive in Long Run: Integrating green practices for long-term business sustainability (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The business sustainability in the long run is affected by various factors. One of such important factor is going green. In order to sustain in business, entrepreneurs have to go green. During last 30 years or more, the world has seen a big movement towards environment. Many people, including movie and TV actors, musicians, politicians and scientists, are giving away social messages about the importance of creating an environmental conscience society. Environmental issues have been transmitted in various modes, emphasizing on what “common people” should do on their personal and business life. So Green Entrepreneurship is just about taking conscious action in day to day activities of business to address this problem. These actions can be as simple as creating a recycle and reuse policy in the company for materials or it can be more advanced, as using new techniques that reduce emissions of gases on production or using cleaner energy from renewable sources. This conceptual paper discusses the concept of green entrepreneurship by relating business manufacturing process with the Organisation for Economic Co-operation and Development (OECD) Sustainable Manufacturing Indicators. In this paper, basic seven OECD principles are discussed and author has attempted to elaborate how an entrepreneur can go green at every step to sustain business in long run.